2005
DOI: 10.1002/jnr.20391
|View full text |Cite
|
Sign up to set email alerts
|

A humanin derivative, S14G‐HN, prevents amyloid‐β‐induced memory impairment in mice

Abstract: Humanin (HN) is a 24-amino acid peptide that protects neuronal cells from death caused by Alzheimer's disease (AD)-related genes and amyloid-beta (Abeta). Multiple studies have revealed its biochemical and neuroprotective characteristics in vitro; however, little has been known regarding whether HN is effective in vivo in AD model systems. We examined the effect of S14G-HN, a 1,000-fold more potent derivative of HN in vitro, on amnesia induced by Abeta25-35 in mice. The Y-maze test revealed that at least 50 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 55 publications
3
67
1
Order By: Relevance
“…In this model, loss of cholinergic neurons was induced by Ab injection. 18 Indeed, we confirmed that injection of Ab(1-40) significantly induced loss of cholinergic neurons in the basal forebrain. However, there was no significant increase in the number of cholinergic neurons in mice transfected with the HGF gene as compared with mice transfected with control vector (data not shown).…”
Section: Molecular Mechanisms Of Alleviation Of Ab-induced Cognitive supporting
confidence: 68%
See 1 more Smart Citation
“…In this model, loss of cholinergic neurons was induced by Ab injection. 18 Indeed, we confirmed that injection of Ab(1-40) significantly induced loss of cholinergic neurons in the basal forebrain. However, there was no significant increase in the number of cholinergic neurons in mice transfected with the HGF gene as compared with mice transfected with control vector (data not shown).…”
Section: Molecular Mechanisms Of Alleviation Of Ab-induced Cognitive supporting
confidence: 68%
“…Intracerebroventricular administration was carried out in accordance with the procedure previously described. 18 Briefly, mice were anesthetized with isoflurane gas and xylazine and ketamine, and Ab(1-40) (200 pmol per 5 ml) was injected intracerebroventricularlly into mice, aimed at 1-1.5 mm lateral to the left of the midline, 0.5 mm posterior to the bregma and 3 mm depth using a 100-ml Hamilton syringe with a 27-gauge needle.…”
Section: Ab Injection Modelmentioning
confidence: 99%
“…Animals were acclimated to a climate-controlled room with a constant 12 h light/dark cycle (12 h on, 12 h off) for a week prior to the initiation of drug administration. At 6 weeks of age, the ICR mice received an intracerebroventricular injection of Aβ (400 ρmol/mouse) or control solution (PBS) as described previously, 55,56 with minor modifications. Briefly, mice were anesthetized with isoflurane gas, and Aβ (400 ρmol/2 uL) or control solution (PBS) was slowly injected (0.2 uL/min) bilaterally into the lateral ventricles (0.2 mm posterior to bregma, 1.0 mm lateral to midline, and 3.1 mm ventral to the brain surface) using a stainless-steel injection needle (26 gauge) connected to a 10 μL Hamilton micro-syringe (Hamilton).…”
Section: Cell Viability Analysismentioning
confidence: 99%
“…19 Swimming was video tracked, and latency, path length, swim speed, and cumulative distance from the platform were analyzed by AnyMaze (Stoelting Co).…”
Section: Behavioral Proceduresmentioning
confidence: 99%